Degradation studies of pharmaceutical drugs using fixed bed reactor incorporating dual effect of photocatalysis and photo-Fenton - Talwar, Steffi (My University, 2020)
Developing countries, like India, has emerged as the world's third largest producer of pharmaceutical drugs. Large amount of these pharmaceuticals have been detected in the aquatic systems over the past few years. Failures of conventional technologies have prompted researchers to work in some advanced areas for handling these kinds of contaminants. The Advanced Oxidation Process (AOPs) like photo-Fenton and photocatalysis have gained wide popularity among the researchers due to their capability of treating wide range of pollutants. But certain limitations like increase in the treatment time, electron hole recombination, separation and recovery of the catalyst, high dosage of oxidant, generation of the iron sludge, suitable reactor designing have posed hurdles in the scale-up path of these techniques. In the present study the best efforts have been made to overcome these hurdles faced by the individual AOPs (photo-Fenton and photocatalysis) by introducing a novel concept of fixed-bed in-situ dual effect. The work focuses on the incorporating the dual effect of photocatalysis and photo-Fenton using composite beads for the degradation of pharmaceutical drugs i.e. Phenazone (PHZ) and Metronidazole (MTZ) in fixed mode. The study has been executed by fabricating a composite made up of Fuller’s earth (FE) and Foundry sand (FS) with a coating of TiO2. FE and FS being the natural source of iron has been used for the photo-Fenton reactions to take place. The leaching of iron from the composite support (in acidic conditions) along with the surface active TiO2 layer executes the dual effect. For the study to execute two types of reactors i.e. batch reactor and continuous reactors were employed. For the batch scale trials, two types of composite beads prepared of FE and FE+FS were employed for the degradation of PHZ. Although both type of beads showed the degradation but FE beads were not durable enough in terms of strength and stability hence, for further studies FE+FS beads were employed. These composite beads were used for the parametric optimization for the degradation of both the drugs PHZ and MTZ. Box Behnken design (BBD) has been employed for the optimization of various parameters. An artificial neural network model coupled with the genetic algorithm was employed for the optimization of various parameters for MTZ.Various parameters like the surface area covered in terms of number of beads, dosage of the oxidant, time, pH, the intensity of light were studied for the estimation of degradation efficiency. The in-situ dual effect leads to 80% degradation of PHZ and 91% degradation of MTZ. Kinetics studies revealed the increase in the reaction rate constant (k) to 5 folds for PHZ, thus envisages degradation to be achieved at a faster pace. 81.37% of synergy was observed in the case of MTZ for the dual process. The variability in the recyclability studies varies as per the phase of the research work. As same composite beads were used for the complete study and no new composite beads were prepared during the research work. The beads were durable enough to be recycled for more than 70 recycles while maintaining their catalytic activity for both the processes. For the confirmation of catalytic activity of photocatalysis and photo-Fenton process even after recycles, various characterizations including XRD, SEM-EDS, FTIR, Raman and UV-DRS were performed. The mineralization of the compounds PHZ and MTZ were confirmed in terms of reduction in COD, TOC and the formation of various ions like nitrates, nitrites and ammonical ions. The intermediates formed during the reaction were analyzed using GC-MS and the probable degradation mechanism was proposed for both PHZ and MTZ. Pilot-scale fixed bed reactors employed in once-through mode were studied for the degradation of MTZ and PHZ. Same composite beads made of FE+FS were employed for encompassing the in-situ dual effect of photocatalysis and photo-Fenton. Pilot scale three reactors in series and compound parabolic concentrator (CPC) were employed for the studies. These reactors were studied in terms of approaching the plug plow for the better implementation of the process. The complete optimization studies were conducted for the pollutants (MTZ and PHZ). The extended recyclability of the beads were studied for >80 recycles and was confirmed from the characterizations. The complete mineralization of the compounds were also conducted. For the real time view of the dual process cost analysis has also been conducted. The overall cost for the treatment of 1L of solution came out to be less than 0.1 US $ which signifies its potential for commercial scale viabilities. The scale up cost analysis was also executed for real scale applications. Further, for the authentication of the results of dual effect, the study has been extended to the real industrial wastewater. The study was conducted in batch mode and then was implemented in continuous mode. For the batch scale studies, the significant reduction in Chemical Oxygen demand (COD) (81%) along with the decrease in the treatment time by 60-70 min was observed as compared to the exclusive processes of photo-Fenton and photocatalysis. Optimization of various parameters using continuous mode reactor has been studied in the sunlight and 75% reduction was observed after 5 h in recirculation mode.The study has also been extended to the plug flow approaching reactor in once through mode. 55% of COD removal after 45 minutes proves the effectiveness of the process using three reactors in series. Wastewater which was treated was evaluated to be non-toxic as verified from the GC-MS analysis as well as the Kirby-Bauer test. Various characterizations were performed to validate the importance of the dual effect (presence of iron as well as the activity of TiO2). Recyclability of the catalyst even after subsequent recycles confirmed the economic efficacy of the process.
Keywords: Photocatalysis; Photo-Fenton; pharmaceutical drugs; Fixed bed reactor; Advanced Oxidation Process